Improvement of Olfactory Function With High Frequency Non-invasive Auricular Electrostimulation in Healthy Humans - Maharjan, Ashim; Wang, Eunice; Peng, Mei; Cakmak, Yusuf O. (Frontiers in Neuroscience, 2018)
In past literature on animal models, invasive vagal nerve stimulation using high frequencies has shown to be effective at modulating the activity of the olfactory bulb. Recent advances in invasive vagal nerve stimulation in humans, despite previous findings in animal models, used low frequency stimulation and found no effect on the olfactory functioning. The present article aimed to test potential effects of non-invasive, high and low frequency vagal nerve stimulation in humans, with supplementary exploration of the orbitofrontal cortex using near-infrared spectroscopy. Healthy, male adult participants (n=18) performed two olfactory tests (odour threshold test and supra-threshold test) before and after receiving high-, low frequency vagal nerve stimulation and placebo (no stimulation). Only high frequency, non-invasive vagal nerve stimulation was able to positively modulate the performance of the healthy participants in the supra-threshold test, with significant differences in near-infrared spectroscopy recordings of the right hemispheric, orbitofrontal cortex. The results from the current article implore further exploration of the neurocircuitry involved under vagal nerve stimulation and the effects of non-invasive, high frequency, vagal nerve stimulation towards olfactory dysfunction which showcase in Parkinson's and Alzheimer's Diseases.